Reisebusmarketing und Reisebusimage in Deutschland. Eine aktuelle Bestandsaufnahme. - Polzin, Dietmar W. (Deutscher Verkehrs-Verl., 2010)
In der öffentlichen Diskussion wird dem Reisebus oft ein schlechtes "Image" bescheinigt. "Billige Seniorenreisen" oder "Kaffeefahrten" stehen dann synonym für Busreisen. Bei einem realistischen Vergleich der Vor- und Nachteile mit anderen Verkehrsträgern müsste die Busreise eigentlich einen höheren Marktanteil besitzen. Der Beitrag versucht, die Hintergründe zu beleuchten. Grundlagen zum Dienstleistungsimage bieten die Basis für eine Bestandsaufnahme des Reisebusimages und den damit direkt verbundenen Marketingaktivitäten der deutschen Reisebusunternehmen.

The image associated with a product or a service is a decisive factor - prior to any consideration given to costs - whenever a selection is made as, for instance, in the case of coach travel. A poll of fifty-one coach operators has given us an idea of the image associated with coach travel in Germany. About two thirds of the operators questioned have mentioned an essentially negative image of coach travel among the public in general, citing such factors as old fashioned, uncomfortable and slow. Questions about coach operators' current marketing efforts have thrown light on certain shortcomings, which may also be a contributing factor to the flawed image associated with coach travel. lmage perceptions vary greatly according to the target group questioned, showing notable differences between existing clients and non-clients. The image is predominantly positive among existing clients since they appreciate coach travel-related aspects such as social gatherings, value-for-money, comfortable travel, safety and flexibility much more than the other target group questioned in this sample survey. Based on this poll of entrepreneurs, an analysis of relevant literature and the subsequent verification of the findings collected in the course of discussions held with experts from various trade associations, we have been able to formulate recommendations deemed essential for developing the coach travel market in future.
Coach travel in Germany - aspects of marketing and image.
Keywords: Öffentlicher Verkehr; Verkehrsmittel; Bus; Marketing; Freizeitverkehr; Fremdenverkehr; Verkehrsunternehmen; Bestandsaufnahme; Reisebus; Image; Tourismus